Revitalization of the Novel of the Fire Smoke Cloud By Korrie Layun Rampan (Antropolinguistic Study) - Fajarika Ramadania; Haris Supratno; Setya Yuwana; Suhartono; Darni; Udjang Pairin (Britain International for Academic Research (BIAR-Publisher), 2021)
The revitalization of Api Awan Asap Novel by Korrie Layun Rampan (Anthropology Study), This study aims to (1) describe language, (2) describe technological systems, (3) describe livelihoods, (4) describe arts, and (5) describe systems religion in the novel Api Cloud Asap by Korrie Layun Rampan. The method in this study uses a descriptive analysis method and an anthropological approach that includes aspects of literary anthropology. The data source in this study is the novel Api Awan Asap by Korrie Layun Rampan. The collection technique in this research is text observation technique and interpretive descriptive technique. The results of this study can be concluded as follows: (1) the language system contained in the Api Awan Asap novel, namely the Dayak Benuaq language and English, (2) the technological system described in the Api Awan Asap novel such as: lou, bivouac, ulin, ketinting , sharp weapons, ulap, ulap doyo, jewelry, (3) the livelihood system described in the novel Api Awan Asap, such as gardening, hunting, berhuma, cutting down forests, and businessmen, (4) the arts described in the novel Api Awan Asap, namely musical instruments, sculpting, weaving, dancing, singing, and weaving, (5) the religious system described in the novel Api Awan Asap, namely the application ceremony, wedding ceremony, magic, legend, and customary law ceremonies.